PENINGKATAN DISPOSISI MATEMATIKA MAHASISWA STKIP PESISIR SELATAN PADA MATA KULIAH STATISTIKA DASAR DENGAN PENERAPAN PROBLEM BASED LEARNING - Okviani Syafti (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2019)
Disposition is a character or personality that is needed for an individual to succeed. Students need a mathematical disposition to persevere in the face of problems, take responsibility in their learning, and develop good work habits in mathematics. However, the mathematical disposition of STKIP Pesisir Selatan students while attending basic statistics lectures is still far from expectations. This is seen from the results of a questionnaire that 56% of students who do not like elementary statistics courses. In addition they lack confidence in solving problems in mathematics. For this reason, a learning model is needed to overcome them. One model that can be used is problem based learning. With learning like this will form the tendency of students to be diligent, conscientious, never give up, see a problem from a variety of different perspectives to get a solution so that when the student successfully resolves a given problem, it will give a sense of pleasure, satisfaction and confidence appears. The purpose of this study is to find out how to increase the mathematical disposition of STKIP Pesisir Selatan students in basic statistics courses before and after learning problem based learning and whether the improvement is significant. All populations were sampled, namely students of mathematics and ICT education courses taking basic statistics courses in the even semester 2018/2019. This type of research is Quasi Exspriment with One Group Pretest-Posttest Design. The research data were obtained from a questionnaire given before and after the experiments were carried out. Data analysis used N-gain test to measure the increase in mathematical disposition and continued by paired sample t test to see the significance of the increase. The results of the analysis show that the increase in mathematical disposition of STKIP Pesisir Selatan students with the application of problem based learning in basic statistical subjects has increased quite well, but the increase that occurred was not significant.